Negative Pressure Pulmonary Edema- Case Series and Review of Literature - Bhattarai, B; Shrestha, S (Kathmandu University Medical Journal, 2012)
Post obstructive pulmonary edema (POPE) also known as Negative pressure pulmonary edema (NPPE)is potentially life threatening complication. It occurs in about 0.1% of anesthetics and is related to upper airway obstruction. Two types have been described in literature. Different etiology has been attributed to development of Negative pressure pulmonary edema. Early identification and treatment of predisposing factor along with proper monitoring of this complication early treatment should be instituted because resolution is also fast and in most cases without residual effects. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6352 Kathmandu Univ Med J 2011;9(4):310-4